Risk of Dysphonia in Theater Actors: Proposal for a Screening Protocol - Ferrari, Eloisa Pinheiro; da Trindade Duarte, João Marcos; Simões-Zenari, Marcia; Vilela, Nadia; Master, Suely [UNESP]; Nemr, Katia (Elsevier, 2023)
Objective: To propose a Dysphonia Risk Screening Protocol for Actors (DRSP-A), test its usability in conjunction with the General Dysphonia Risk Screening Protocol (G-DRSP), determine the cut-off point for a high risk of dysphonia in actors, and compare the risk of dysphonia between actors with and without voice disorders. Method: Observational cross-sectional study with 77 professional actors or students. The questionnaires were applied individually and the total scores were summed to calculate the final score of the Dysphonia Risk Screening (DRS-Final). The validity of the questionnaire was verified from the area under the Receiver Operating Characteristic (ROC) curve, and cut-offs were obtained based on diagnostic criteria for screening procedures. Voice recordings were collected for auditory-perceptual analysis and subsequent division into groups with and without vocal alteration. Results: The sample showed a high risk of dysphonia. Higher scores in the G-DRSP and in the DRS-Final were found in the group that presented vocal alteration. The cut-off points established for the DRSP-A and DRS-Final were 0.623 and 0.789, respectively, with higher degrees of sensitivity than specificity. Thus, above these values, the risk of dysphonia is greater. Conclusion: A cut-off value was calculated for the DRSP-A. This instrument was proven to be viable and applicable. The group with vocal alteration had a higher score in the G-DRSP and DRS-Final, but there was no difference in the DRSP-A.
Keywords: Occupational health; Surveys and questionnaires; Vocal quality; Voice; Voice disorders